Pengaruh CAR, ROA, Inflasi dan Kurs Terhadap Tingkat Suku Bunga Deposito Bank” - Elok Dwi Vidiastutik; Trivosa Aprilia Novadiani; Haidi putri (Fakultas Ekonomi Universitas Panca Marga, 2016)
This research determinethe effect Capital Adequacy Ratio (CAR), Return On Assets (ROA), Inflation and exchange rate of the Bank Deposit. This research, especially for investors as the balance in the investment decision-making in the banking sector. Data analysis technique used is multiple linear regression using the F test and t test. Where the performance of banks consisting of a CAR, ROA, Inflation and exchange rate also a positive significant effect on interest rates on foreign currency bank deposits. And based on model test showed that significantly influence the performance of the bank deposit interest rates. Key word: Capital Adequacy Ratio (CAR), Return On Assets (ROA), Inflation, exchange rate and Bank Deposit